(untitled) (Journal of Applied Oral Science, 2022)
The aim of this study was to evaluate the clinical and radiographic periodontal status of impacted permanent maxillary central incisors (Mx.1) after a long term of orthodontic traction. Methodology: This split-mouth study evaluated a sample of 11 patients (five females, six males) treated with Mx.1 unilateral traction one to 28 years after the removal of orthodontic appliances. The traction Group (TG) consisted of 11 Mx.1 and the Comparison Group (CG) comprised 11 spontaneously erupted contralateral Mx.1. High-resolution CBCT exams of central incisors were performed using Accuitomo (J. Morita, Kyoto, Japan). Cross-section imagens passing through the center of maxillary central incisors were used to measure buccal and lingual alveolar bone level. Presence of fenestration, root dilacerations, root coverage, and position of the root apex were also assessed in the same images. Clinical parameters included periodontal probing depth, attachment level, gingival bleeding index, plaque index, degree of gingival recession, amount of gingival mucosa, and evaluation of interproximal papilla and black triangle. Digital model analysis included an assessment of clinical crown height and width. Intergroup comparisons were performed using paired t-, McNemar’s, and Wilcoxon tests (p<0.05). Results: Compared to CG, we found a significantly thinner labial bone plate thickness in TG at the middle (p=0.000) and apical (p=0.009) root level. We also observed an apical displaced labial bone crest level in TG (p=0.000). The Traction Group showed a greater frequency of root dilacerations and gingival recessions, a decreased amount of keratinized mucosa, and a decreased clinical attachment level at the labial aspect compared to contralateral teeth. Conclusions: A decreased thickness and height of labial alveolar bone and gingival recessions were found in maxillary central incisors 15 years after orthodontic traction. Though incisor traction might cause some periodontal impact, differences are acceptable under a clinical point of view considering the cost-benefit ratio.